L’Antiphonaire d’Oosteeklo et son enlumineur (Cornelia van Wulfschkercke ?) - Dominique Vanwijnsberghe (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Despite its importance for the history of Flemish book painting, the Oosteeklo Antiphonal, kept at the library of the Ghent Museum of Fine Arts, has been largely neglected by art historians. A remarkable colophon discloses the identity of its patroness, Quentine de Mastaing, abbess of the Cistercian convent of Oosteeklo. It also mentions the name of the two scribes and the year of completion of the manuscript (1498). Moreover, the historiated initials can be related to a documented artist: the celebrated Cornelia van Wulfschkercke, Carmelite of the Sion convent in Bruges, to whom an important body of works has been attributed. Two other manuscripts by the same hand are presented, an ideal opportunity to assess the validity of an identification that remains, at this stage of research, a working hypothesis.